We average unbeautiful watchers : fan narratives and the reading of American sports - Cohan, Noah (Sports, media, and society., 2019)
"Sports fandom--often more than religious, political, or regional affiliation--determines how millions of Americans define themselves. In We Average Unbeautiful Watchers, Noah Cohan examines contemporary sports culture to show how mass-mediated athletics are in fact richly textured narrative entertainments rather than merely competitive displays. While it may seem that sports narratives are "written" by athletes and journalists, Cohan demonstrates that fans are not passive consumers but rather function as readers and writers who appropriate those narratives and generate their own stories in building their sense of identity. Critically reading stories of sports fans' self-definition across genres, from the novel and the memoir to the film and the blog post, We Average Unbeautiful Watchers recovers sports games as sites where fan-authors theorize interpretation, historicity, and narrative itself. Fan stories demonstrate how unscripted sporting entertainments function as identity-building narratives--which, in turn, enhances our understanding of the way we incorporate a broad range of texts into our own life stories. Building on the work of sports historians, theorists of fan behavior, and critics of American literature, Cohan shows that humanistic methods are urgently needed for developing nuanced critical conversations about athletics. Sports take shape as stories, and it is scholars in the humanities who can best identify how they do so--and why that matters for American culture more broadly"--